PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT CAHAYA EXPRESS DI KOTA BATAM - Oskar,; Tiurniari Purba, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Cahaya Express is a private company engaged in the freight forwarding business that provides goods shipping services for containers fully loaded (Full Container) or those with a small load via sea shipping. Facilities and service quality variables at PT Cahaya Express are still lacking, of course it will bring negative effects if solutions are not sought to overcome them. Therefore, this study aims to determine and analyze the effect of facilities and service quality on customer satisfaction of PT. Cahaya Express. This study has a population of 219 customers. The sample used is a simple random sampling technique that is said to be simple because the sampling of members of the population is done randomly without regard to existing strata. The results of the sample were 141 customers with the results of the Slovin formula calculation. Data collection techniques in this study using a questionnaire. The data processing method in this study uses SPSS 25. Based on the test results, it states that the facilities and service quality simultaneously have a positive and significant influence on customer satisfaction.